2016
DOI: 10.1080/02626667.2016.1240870
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual modelling to assess the influence of hydro-climatic variability on runoff processes in data scarce semi-arid Andean catchments

Abstract: Using hydro-meteorological time series of 50 years and in situ measurements, the dominant runoff processes in perennial Andean headwater catchments in Chile were determined using the hydrological model HBV light. First, cluster analysis was used to identify dry, wet and intermediate years. From these, sub-periods were identified with contrasting seasonal climatic influences on streamflow. By calibrating the model across different periods, impacts on model performance, parameter sensitivity and identifiability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Precipitation-Runoff Modeling System (PRMS) (Markstrom et al 2015 2017). The most recent PRMS release (version 4, applied in the present study) uses daily time steps, which is consistent with the widespread availability of historical, spatially-distributed daily meteorological data for large continental regions (e.g., GPCC, www.esrl.noaa.…”
Section: Precipitation-runoff Modeling System (Prms)mentioning
confidence: 99%
“…Precipitation-Runoff Modeling System (PRMS) (Markstrom et al 2015 2017). The most recent PRMS release (version 4, applied in the present study) uses daily time steps, which is consistent with the widespread availability of historical, spatially-distributed daily meteorological data for large continental regions (e.g., GPCC, www.esrl.noaa.…”
Section: Precipitation-runoff Modeling System (Prms)mentioning
confidence: 99%
“…The continuing increase in the demand for water and climate changes are expected to have major impacts on water resource availability (Dakhlaoui et al 2017;Nauditt et al 2017;Guermazi et al 2019). Hydrological models are often used to evaluate short-term and long-term changes in water resource availability (see e.g., Ruelland et al 2012;Milano et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Applying a regional hydrological model implies its repeated use everywhere within a region, using a global set of parameters, which are generally transferred from gauged catchments (Engeland & Gottschalk, 2002;Seibert & Beven, 2009). Therefore, it seems necessary to evaluate the modelling robustness and, particularly, the transposability of the calibrated parameters to contrasted climate and/or anthropogenic conditions (Nauditt, Birkel, Soulsby, & Ribbe, 2016). Thirel et al (2015) suggested a calibration and evaluation protocol for dealing with changing catchments, highlighting the advantages of the Differential Split-Sample Test (DSST; KlemeĆĄ, 1986).…”
mentioning
confidence: 99%